The implications of NICE guidelines on the management of children presenting with head injury - Dunning, J (2004)
Background: NICE guidelines for the management of head injury were published in June 2003. Their recommendations differ markedly from previous guidelines published by the Royal College of Surgeons (RCS). In place of skull radiography and admission, computed tomography (CT) is advocated. The impact of these guidelines on service provision in the UK is unknown. Methods: Data on all clinical correlates of children presenting with any severity of head injury was collected in three hospitals in the northwest of England. The current skull radiograph (SXR), CT scan, and admission rates were determined. The rates of SXR, CT scan, and admission that should have occurred when following either the RCS or NICE guidelines were then determined. Results: Data from 10 965 patients who attended three hospitals between February 2000 and August 2002 was studied. Twenty five per cent of patients received a SXR, 0.9% a CT scan, and 3.7% were admitted. Strict adherence to the RCS guidelines would have resulted in a 50% SXR rate, a 1.6% CT scan rate, and a 7.1% admission rate. Adherence to NICE guidelines would result in a 0.3% SXR rate, an 8.7% CT scan rate, and a 1.4% admission rate, although the CT rate would drop to 6.3% if vomiting three or more times in the under 12s was used instead of more than one vomit. Conclusions: The new NICE guidelines do not increase the workload caused by patients attending with head injury but they move their management from the observation ward to the radiology department.